Role of the neuropilin ligands VEGF164 and SEMA3A in neuronal and vascular patterning in the mouse. - Vieira, J; Schwarz, Q; Ruhrberg, C (2007)
Blood vessels and neurons use similar guidance cues to control their behaviour during embryogenesis. The semaphorin SEMA3A was originally identified as a repulsive cue for developing axons that acts by signalling through receptor complexes containing NRP1 and A-type plexins. SEMA3A also competes with the VEGF164 isoform of vascular endothelial growth factor for binding to NRP1 to modulate the migration of endothelial cells in vitro. Surprisingly, we have found that SEMA3A and semaphorin signalling through NRP1 were not required for blood vessel development in the mouse. Moreover, we found that there was no genetic interaction between SEMA3A and VEGF164 during vasculogenesis or angiogenesis. Our observations suggest that in vivo vascular NRP1 preferentially confers VEGF164 signals, whilst axonal NRP1 preferentially transmits SEMA3A signals.